Women’s roles and opportunities in cassava value chains in Son La province in Vietnam: A technical report - Kawarazuka, Nozomi; Bui, Trang; Phan, CH.; Hoang, TX. (International Potato Center, 2021)
Cassava is a major export-oriented cash crop in Vietnam. Unlike other cash crops, such as coffee, fruits, and maize, cassava requires limited agricultural input and labour and can grow in nutrient-poor uplands. Research on cassava breeding, seed systems and value chains in Southeast Asia is increasingly focused on market-oriented aspects such as developing hybrid varieties favourable to the cassava starch industry, disease control on large scale farms, and seed systems driven by the private sector. However, in the northern mountainous areas of Vietnam, ethnic minority farmers use cassava roots, leaves and sticks for numerous reasons, including starch production, fish and animal feed, firewood, and home consumption. Women play significant roles in those non market-oriented activities (often collecting left-over small roots in the field, drying roots, and cutting leaves and stems) but little is known about how this work influences women’s roles, decision-making and opportunities in cassava value chains. Hence, this study provides that data with an eye to see how women may find more opportunity for creating small business enterprises with cassava. Fieldwork was conducted in July 2021 in the Chieng La commune (Thuan Chau district) and the Muong Bon Commune (Mai Son district). Findings show that although women are less involved in decision making on cassava production and overall agricultural investment, they play important roles in cassava production and post-harvest activities. Therefore, it is extremely important to collect and analyze women’s preferences, concerns and constraints in cassava research and interventions. In the conclusion, we highlight additional areas for research on this topic.